2020
DOI: 10.7196/samj.2020.v110i7.14903
|View full text |Cite
|
Sign up to set email alerts
|

South African healthcare workers and COVID-19: a shared responsibility to protect a precious and limited resource

Abstract: South African healthcare workers and COVID-19: A shared responsibility to protect a precious and limited resource To the Editor: Healthcare workers (HCWs) in African countries face high risks of occupational exposure to many pathogens, including tuberculosis, measles, HIV and Ebola. [1,2] The novel coronavirus SARS-CoV-2 poses an arguably greater threat to African HCWs than any other infectious agent to date. Data from countries with established epidemics show that HCWs experience high rates of COVID-19 infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…HCWs in Africa are familiar with occupational exposure to many pathogens; however, SARS-CoV-2 currently poses an arguably greater threat to HCWs than any other infectious agent to date. (11) Studies suggest that HCWs have a COVID-19 infection rate of up to 11% which is higher than in the general population (12) with studies from the United Kingdom and the USA demonstrating that frontline HCWs were 3.4 times more likely than the general population to test positive for COVID-19, after adjusting for testing patterns. (13) The current study demonstrated that 24% of the HCWs based in the ED developed symptomatic COVID-19 over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…HCWs in Africa are familiar with occupational exposure to many pathogens; however, SARS-CoV-2 currently poses an arguably greater threat to HCWs than any other infectious agent to date. (11) Studies suggest that HCWs have a COVID-19 infection rate of up to 11% which is higher than in the general population (12) with studies from the United Kingdom and the USA demonstrating that frontline HCWs were 3.4 times more likely than the general population to test positive for COVID-19, after adjusting for testing patterns. (13) The current study demonstrated that 24% of the HCWs based in the ED developed symptomatic COVID-19 over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…HWs remain at the highest risk of SARS-CoV-2 infections globally and in South Africa (Figure 1). 15,16 World Health Organisation (WHO) estimates indicated that up to 14% of COVID-19 cases were attributable to HWs. 17 The incidence of infection in HWs at a major tertiary hospital in Gauteng province, South Africa was reported to be 132.1 infections per 1000 person-months (95% confidence interval, 111.8-156.2).…”
Section: Hw Infections and Worker's Compensation Claimsmentioning
confidence: 99%
“…In this regard, nurses were required to work longer hours, under increased restrictions and often unfamiliar settings, while continuously wearing personal protective equipment (PPE) (Dramowski et al, 2020). Physical exhaustion, separation from family, and losing loved ones and colleagues resulted in nurses' evaluating their career paths.…”
Section: Introductionmentioning
confidence: 99%
“…Physical exhaustion, separation from family, and losing loved ones and colleagues resulted in nurses' evaluating their career paths. The pressures of the pandemic deepened the challenges confronting nurses within their working environment (Dramowski et al, 2020). Nurses are expected to deliver quality healthcare, save lives and achieve set organisational goals, despite the challenges they experience (Shamian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%